(untitled) (Studia theodisca, 2019)
Austrian and German intellectuals were often disappointed when visiting contemporary Greece. This article examines various aspects of this tension between expectation and disappointment, as recorded in travel literature dating from the mid-nineteenth to the early twentieth century. It focuses on the nostalgia for Ancient Greece and its disillusionment due to the immense temporal distance. It also examines the portrayal of the landscape as a guarantee of continuity, in order to overcome this disappointment. To this Ancient-centered nostalgia this article juxtaposes one of a different kind, this time related to the Byzantine tradition. This nostalgia can be found in the German and Austrian travel literature that describes visits to Greek monasteries, especially on the Athos peninsula, and reaches its peak in the mystical overtones of travellers’ accounts in the twentieth century.